Effects of Verbal Student-Made Models Strategy on Senior School Students’ Performance in Organic Chemistry in Jos, Nigeria - John, Dorcas Peter; Afolabi, Kayode Ojo; Akanmu, Alex Morenikeji; Ameen, Khadijat Saka; Mohammed, Ridwan Enuwa; Imam, Bashirat Titilope (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
The verbal student-made approach is based on Albert Bandura's (1977) observational learning theory, which proposed that learning is enhanced when concepts and ideas are slowly explained and described. To find out how verbal students' created models affected the organic chemistry performance of senior school II students, this study was conducted. For the investigation, two hypotheses and two research questions were developed. A quasi-experimental research approach was utilised, incorporating two pre-existing classes alongside a non-equivalent control group design. The study involved a total of 425 Senior Secondary II students specialising in chemistry within the Jos Metropolis, Nigeria. A total of 78 pupils were purposefully chosen to make up the study's sample. A control group and an experimental group were allocated to the classrooms for the verbal Student-Made Model technique. The chemistry teachers from the selected schools received training and were actively engaged in the study. Data collection was conducted using the Organic Chemistry Performance Test (OCPT), which demonstrated a reliability coefficient of 0.89. This assessment tool was developed by the researcher and subsequently validated by three subject matter experts. All of the hypotheses were evaluated using Analysis of Covariance (ANCOVA), and mean and standard deviation (SD) were used to analyse the gathered data. According to the study, students' performance differed significantly, regardless of gender, when taught organic chemistry using VSMS compared to the traditional technique (F (1,75) = 32.85, p <.05). It was suggested that the senior schools continue to employ verbal models created by students to teach and master organic chemistry principles.